Effect of Aerobic Exercise on Blood Glucose Among Those with Prediabetes: A Systematic Review and Meta-Analysis - Tianyi Jiang; Zichen Ye; Qu Lu; Peixia Cheng; Qi Gao (Life)
Prediabetes, a state between normoglycemia and diabetes, is increasingly affecting population health; thus, it should not be overlooked. This systematic review and meta-analysis aimed to explore the efficacy of aerobic exercise on blood glucose indicators among those with prediabetes. Five databases, including PubMed, Embase, the Cochrane Library, Web of Science, and CINAHL, were searched up to September 2024 to identify randomized controlled trials measuring the effect of aerobic exercise on blood glucose levels among individuals with prediabetes. Data on fasting blood glucose (FBG), 2-h postprandial plasma glucose (2hPG), and hemoglobin A1c (HbA1c) were extracted. Subgroup analyses were conducted based on intervention duration, weekly exercise duration, and volume. In total, 2518 relevant records were initially retrieved, and 16 studies were included in this systematic review, with 14 providing sufficient data for meta-analysis. Compared to the control group, the weighted mean difference (MD) for FBG, 2hPG, and HbA1c was −1.33 (95%CI: −1.87, −0.89), −1.00 (95%CI: −1.60, −0.39), and −1.05 (95%CI: −1.49, −0.61), respectively. Subgroup analysis showed that pooled effect size for FBG, 2hPG, and HbA1c was greater in the subgroup subjected to ≥48 weeks of intervention compared to the subgroup subjected to ≤24 weeks of intervention, although only the difference in FBG was significant (p < 0.05). Weekly exercise longer than 180 min/week led to greater reductions in FBG, 2hPG, and HbA1c compared to weekly exercise shorter than 150 min/week, and only differences in 2hPG were not significant (p > 0.05). Total weekly exercise of 1314–1323 MET·min/week led to greater reductions in FBG and HbA1c levels compared to 975–1080 MET·min/week (p > 0.05). Aerobic exercise effectively decreases FBG, 2hPG, and HbA1c and controls blood glucose levels. The volume and duration of aerobic exercise are important factors affecting the reduction in blood glucose levels, exhibiting a positive correlation within a specific range. Aerobic exercise can serve as a viable therapeutic approach for reducing the risk of diabetes among individuals with prediabetes.